The Tension of Tourism: The Game of Over-Tourism and Sustainable Development in Macau - Cao, Yu; Kong, Zhuoyu (International Journal of Social Sciences and Public Administration, 2024)
This study takes Macau as a case study to explore the dialectical relationship between over-tourism and sustainable tourism, aiming to provide valuable theoretical insights and practical guidance for addressing the global phenomenon of over-tourism. As one of the most attractive tourist destinations in the world, Macau faces significant tourism pressure, particularly in the context of geographical space constraints, where the expansion of the tourism industry creates a sharp contradiction with the city’s carrying capacity. The article begins by analyzing the impact of over-tourism on Macau’s urban space and social structure, revealing the boundary effects of tourism development and the tension between tourism and the quality of life of residents. From a dialectical perspective, the article further examines sustainable tourism as a potential solution to over-tourism, emphasizing that it is not merely a resource management strategy, but a profound cultural and social ethical reflection. This study argues that over-tourism and sustainable tourism are part of an ongoing dynamic process, and that their contradictions are not irreconcilable. Solutions can be found through the integration of cultural identity, social cooperation, and a global perspective.